Manajemen Persediaan pada Koperasi Baitul Qiradh Baburrayan di Desa Wih Nareh Kecamatan Pegasing Kabupaten Aceh Tengah - Muhaimin, Arief; Nugroho, Yoga (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
Production process is the core activity of a manufacturing company. In the production process, a company is required to produce a quality product that meets consumer desires. To carry out production activities, good raw materials must be available and in accordance with the company's production needs. Based on Bank Indonesia Research (2021), downstream coffee shop activities are ranked second as a type of MSME business in the province. This research was conducted from August to November 2022. The object of this research was the Baitul Qiradh Baburrayan Cooperative Business which is located in Wih Nareh Village, Pegasing District, Central Aceh Regency. This research aims to analyze the application of Material Requirement Planning (MRP) which begins by analyzing the master production schedule, list of material requirements, and ends by analyzing the optimal order quantity for each raw material. The method used in this research is quantitative methods. carried out on green bean products, it can be seen that demand forecasting uses the Single Moving Average (5 Months) method. Because from the calculation of the Single Moving Average (5 Months) method, the demand for green beans in May is 3,712 kg of green beans per day, 111,360 kg of fruit per month. There are several steps in MRP, namely netting, lotting, offsetting and exploitation. The MRP calculation using the Economic Order Quantity method is 41.17 kg/order